Security System Exploitation on Domains and Subdomains of UIN Syarif Hidayatullah Jakarta - Thoyyibah T; Wasis Haryono; Tomi Hardi (LPPM Universitas Islam 45 Bekasi, 2023)
A computer is a machine that can be used to process any information. In the computer world, crime often occurs. Thus security is needed, for computer systems to avoid various attacks. In the world of computers, especially on the Internet, virus attacks often occur, such as worms, trojans, software piracy and credit card theft problems. Despite the many offers of computer sophistication in processing information, there are still weaknesses that can be exploited by irresponsible parties. This can be detrimental to the rightful owner of the information. So that it can cause small-scale to large-scale damage. Therefore, it is very important for us to know about security exploits so that we can prevent such exploitation and avoid abuse from certain parties. although no system is completely secure. at least we have minimized the possibility by knowing security exploits. Forms of security exploitation generally use various techniques, therefore a security system is needed that is able to overcome these forms of exploitation. This study discusses how to exploit a system and its techniques with the object used is a security system in the domain and subdomain of UIN Syarif Hidayatullah Jakarta. It is hoped that with this research the reader can know and understand the exploitation techniques used so that they can prevent or treat when this exploitation technique is used. The research method used consists of several paths, namely foot printing, scanning, DOOS, Acess, Filtering, finally Covering tracks and creating a backdoor. The research output is the display of the University's network security and its exploitation process.